Efficacy and safety of Omega-3 polyunsaturated fatty acids in adjuvant treatments for colorectal cancer: A meta-analysis of randomized controlled trials - Liu, Haoshuang; Chen, Jingfeng; Shao, Weihao; Yan, Su; Ding, Suying (Frontiers in Pharmacology, 2023)
Background In recent years, various adjuvant chemotherapy treatments for colorectal cancer have been investigated. Many of these have not been demonstrated to be therapeutic, while others, like omega-3 polyunsaturated fatty acids (O3FAs), appear to be more promising. Concerns have been raised concerning O3FA supplements promoting chemoresistance and gastrointestinal side effects such as diarrhea and vomiting. As a result, it is critical to keep track of the efficacy and safety of O3FAs in colorectal cancer treatment. A systematic review focusing on the safety and efficacy of O3FAs in patients receiving adjuvant colorectal cancer treatment is lacking. We systematically reviewed the effectiveness and safety of O3FAs in adjuvant treatments for colorectal cancer. Methods Up to March 2022, published publications were obtained using search terms in digital databases such as PubMed, Web of Science, Embase, and the Cochrane Library. Analyses of subgroups, sensitivity, and inverted funnel plots were also performed. The key outcomes of interest were the rates of infectious and non-infectious complications, length of hospital stay , CRC mortality, tumor necrosis factor-α, C-reactive protein , albumin, BMI, and IL-6. Results After screening 1061 studies, 13 clinical trials (n = 827) and 3 cohort studies (n = 312) with O3FAs in colorectal cancer were included, all of which examined at least one of the efficacy or safety outcomes. In comparison to the control group, O3FAs-enriched nutrition during the perioperative period reduced TNF-α (RR = -1.31, 95% CI: -2.10 to -0.51, P = 0.001), and IL-6 levels (MD = -5.91, 95% CI: -9.80 to -2.02, P = 0.003). No significant difference was found in infectious and non-infectious complications rates, LOS, CRC mortality, CRP, albumin, or BMI. Total parenteral nutrition O3FA supplements reduced the inflammatory states of colorectal cancer patients undergoing adjuvant treatments (TNF-α, MD = -1.26, 95% CI: -2.23 to -0.29, P = 0.01, ; IL-6, MD = -5.98, 95% CI: -9.92 to -2.03, P = 0.003,). Conclusions Our observations indicate that supplementing with O3FAs has little or no effect on patients with colorectal cancer undergoing adjuvant treatment and that long-term inflammatory states can be modified.